2014
DOI: 10.1177/0098628314562677
|View full text |Cite
|
Sign up to set email alerts
|

Highly Prevalent but Not Always Persistent

Abstract: Although past research has documented the prevalence of misconceptions in introductory psychology classes, few studies have assessed how readily upper-level undergraduate and graduate students endorse erroneous beliefs about the discipline. In Study 1, we administered a 30-item misconception test to an international sample of 670 undergraduate, master's, and doctoral students. Analyses indicated that participants identified and rejected the majority of misconceptions, with doctoral students performing better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
(57 reference statements)
0
11
0
3
Order By: Relevance
“…Research in this field (recent reviews: Bensley & Lilienfeld, 2017;Hughes et al, 2013b) seems to confirm this picture. Endorsement of psychological misconceptions is positively related to faith in intuition and negatively related to critical thinking and information literacy (Bensley et al, 2014;Hughes et al, 2013bHughes et al, , 2015Kowalski & Taylor, 2017). Psychological misconceptions decrease-but do not cease to exist-with more psychology training and education (Amsel et al, 2011(Amsel et al, , 2014Gaze, 2014;Hughes et al, 2013aHughes et al, , 2013bHughes et al, , 2015McCarthy & Frantz, 2016;Taylor & Kowalski, 2004).…”
Section: Particular Challenges Of Misconception Correction Related To the Domain Of Psychologymentioning
confidence: 99%
“…Research in this field (recent reviews: Bensley & Lilienfeld, 2017;Hughes et al, 2013b) seems to confirm this picture. Endorsement of psychological misconceptions is positively related to faith in intuition and negatively related to critical thinking and information literacy (Bensley et al, 2014;Hughes et al, 2013bHughes et al, , 2015Kowalski & Taylor, 2017). Psychological misconceptions decrease-but do not cease to exist-with more psychology training and education (Amsel et al, 2011(Amsel et al, , 2014Gaze, 2014;Hughes et al, 2013aHughes et al, , 2013bHughes et al, , 2015McCarthy & Frantz, 2016;Taylor & Kowalski, 2004).…”
Section: Particular Challenges Of Misconception Correction Related To the Domain Of Psychologymentioning
confidence: 99%
“…Other common psychological misconceptions concern "People use only 10% of their brain" (e.g., Higbee and Clay 1998) or "Playing Mozart's music to infants boosts their intelligence" (e.g., Lilienfeld et al 2010). Psychological misconceptions seem to be highly prevalent among both the general population and psychology students (e.g., Furnham and Hughes 2014;Hughes et al 2015;Lilienfeld et al 2010;McCutcheon 1991;McCutcheon et al 1993;Taylor and Kowalski 2004;Vaughan 1977). Furnham and Hughes (2014) identified 37 myths in popular psychology believed by at least two-thirds of their sample of both, the general population and psychology students.…”
Section: Definition and Prevalence Of Psychological Misconceptionsmentioning
confidence: 99%
“…Unfortunately, completing an introductory psychology course may be an inadequate means of reducing misconceptions, as data have suggested mistaken beliefs often persist at the conclusion of those courses (Kuhle, Barber, & Bristol, 2009). Generally, research has shown that misconception endorsement appears to diminish as the number of psychology courses taken increases (Arntzen, Lokke, Lokke, & Eilertsen, 2010; Hughes et al., 2015; Taylor & Kowalski, 2004). However, optimism for this pattern should be restrained as upper-division psychology students have been shown to still endorse a large percentage of misconceptions (Gaze, 2014) as well as even revert back later in their education to endorsing popular myths (Lyddy & Hughes, 2012).…”
Section: Introductionmentioning
confidence: 99%